2017
DOI: 10.1089/neu.2016.4453
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Influence of Apolipoprotein E Status on Cognition or Brain Structure in Professional Fighters

Abstract: The role of the apolipoprotein e4 allele in moderating cognitive and neuroanatomical degeneration following repeated traumatic brain injury is controversial. Here we sought to establish the presence or absence of such a moderating relationship in a prospective study of active and retired boxers and mixed martial arts fighters. Fighters (n = 193) underwent cognitive evaluations, interviews regarding fight history, MRI of the brain, and genetic testing. We used a series of moderator analyses to test for any rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Confounds that may affect an athlete’s CTE etiology include high body mass index and acquired systemic conditions (e.g., diabetes and hypertension) [89], which are general health factors associated with cognitive decline seen in non-CTE age-related dementias such as AD [82]. Although there is a higher incidence of neuropsychiatric disorders in athletes with CTE lesions [66, 96], similar behavioral conditions and brain pathology are seen in subjects without a diagnosis of CTE [8, 12, 37, 104, 108] making it difficult to discern the pathophysiological etiology of these ailments. This conundrum also applies to military veterans with post-traumatic stress disorder that present with neuropsychiatric conditions (e.g., depression) and brain structural abnormalities (e.g., decreased hippocampal volume) similar to CTE [34, 40, 91, 92, 102, 106].…”
Section: Discussionmentioning
confidence: 99%
“…Confounds that may affect an athlete’s CTE etiology include high body mass index and acquired systemic conditions (e.g., diabetes and hypertension) [89], which are general health factors associated with cognitive decline seen in non-CTE age-related dementias such as AD [82]. Although there is a higher incidence of neuropsychiatric disorders in athletes with CTE lesions [66, 96], similar behavioral conditions and brain pathology are seen in subjects without a diagnosis of CTE [8, 12, 37, 104, 108] making it difficult to discern the pathophysiological etiology of these ailments. This conundrum also applies to military veterans with post-traumatic stress disorder that present with neuropsychiatric conditions (e.g., depression) and brain structural abnormalities (e.g., decreased hippocampal volume) similar to CTE [34, 40, 91, 92, 102, 106].…”
Section: Discussionmentioning
confidence: 99%
“…In fighters, thalamic volume decreased by 0.4% (right) and 0.3% (left) with each fight. 24 In a more recent study from the same group, Banks and colleagues 59 continued to find a statistically significant relationship between greater exposure and smaller thalamic volume. Moreover, apolipoprotein E genotype status did not impact this relationship.…”
Section: Thalamic Volume and Exposure To Rhimentioning
confidence: 93%
“…The ε4 allele has also been linked to worse cognitive outcomes following TBI with some studies finding the allele associated with worse memory, processing speed, and overall increased cognitive impairment (144)(145)(146). However, not all studies have found an association with worse cognitive outcome and so further work is needed (147)(148)(149). Currently, the association of the APOE ε4 allele with poor outcomes is thought to be mediated by abnormal lysing of its protein product resulting in neurotoxic byproducts that worsen secondary injury and impair recovery (28).…”
Section: Candidate Gene Studies and Genome-wide Association Workmentioning
confidence: 99%